Treatment of chronic injury associated with Achilles insertional tendinopathy using posterior ankle arthroscopy - Tobias, Cesar Teixeira; Pagnano, Rodrigo Gonçalves; Paim Lima, Thiago Coelho; Mattos e Dinato, Mauro Cesar (Scientific Journal of the Foot & Ankle, 2018)
Ruptures of the calcaneal tendon, when neglected, cause marked disturbance to gait and support at the tip of the foot. Most causes of pain in this region are related to overload injuries. Previous studies have shown that surgical treatment is the best option for chronic injuries. The purpose of this report is to describe a new endoscopic surgical technique used for treatment of chronic injury of the calcaneal tendon by reconstruction with flexor hallucis longus tendon transfer and fixation with an interference screw at the calcaneus in an elderly diabetic patient with signs of Achilles insertional tendinopathy. Level of Evidence V; Therapeutic studies; Expert opinion.